2014
DOI: 10.2190/om.69.3.d
|View full text |Cite
|
Sign up to set email alerts
|

Death on the Digital Landscape: A Preliminary Investigation into the Grief Process and Motivations behind Participation in the Online Memoriam

Abstract: Increasingly, individuals are bonding and maintaining relationships online. These digital representations of ourselves allow us to connect with others in ways previously not possible. One behavior that is growing in online presentations of self is grieving after the death of an individual in our social network. This work investigates the outcomes of online grieving from a transcorporeal communication model perspective, and draws conclusions on the outcomes of online grief behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…Today, many resort to memorial blogs and websites as a way to analyse their thoughts and seek out peer support (DeGroot & Garmack, 2013). Internet discussion groups allow for a richer, more robust dialogue for participants, and provide a simple way to share emotions with the group (Egnoto et al, 2014). Today, the internet is widely available, and a growing number of people with similar problems are seeking out its social networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, many resort to memorial blogs and websites as a way to analyse their thoughts and seek out peer support (DeGroot & Garmack, 2013). Internet discussion groups allow for a richer, more robust dialogue for participants, and provide a simple way to share emotions with the group (Egnoto et al, 2014). Today, the internet is widely available, and a growing number of people with similar problems are seeking out its social networks.…”
Section: Introductionmentioning
confidence: 99%
“…Many loved ones want to preserve their emotional bonds with the deceased child, and photographs offer a way to both preserve the bond and also remember the deceased child. Facing a reality without the one who is deceased is important for the grieving process (Egnoto et al, 2014), and photographs may encourage loved ones to accept the death of a child (Blood & Cacciatore, 2014). In addition, photographs allow parents to create stories to share with others, which is important in various stages of the grieving process and in accepting death.…”
Section: Introductionmentioning
confidence: 99%
“…Three key factors that emerged from Logan et al's (2017) review as warranting further investigation included the participants' own experience of bereave-ment (bereavement status), the anticipation of the death, and the level of social support the bereaved is perceived to already have. In terms of bereavement status, although some studies found greater empathy for and acceptance of bereaved individuals when the supporter had experienced a bereavement themselves (Blair, 2003;Egnoto, Sirianni, Ortega, & Stefanone, 2014;Villa, 2010), other studies noted no relationship between bereavement experience and expectations of the other's grief or intentions to provide support (Bath, 2009, Catlin, 1993, Thompson & Range, 1990, Wagner & Calhoun, 1991. However, these studies focused on the event of bereavement and overlooked the subjective impact of bereavement.…”
Section: Introductionmentioning
confidence: 99%
“…In general, results thus far have acknowledged FB's functions in continuing bonds and confirmed that SNS has altered ordinary grieving rituals, norms, and communication settings, such as the offline and online, the personal and shared, and the private and public grieves. Besides that, FB was said had also helped to strengthen existing relationships among survivors, which it creates new communities of the bereaved and grief-supportive groups on cyberspace (Egnoto, Sirianni, Ortega, & Stefanone, 2014;Giaxoglou, 2015;Kasket, E., 2012;Kern, Forman, & Gil-Egui, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%